2017
DOI: 10.1038/srep42104
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Adipogenic Chemicals in Three Different Cell Culture Systems: Implications for Reproducibility Based on Cell Source and Handling

Abstract: The potential for chemical exposures to exacerbate the development and/or prevalence of metabolic disorders, such as obesity, is currently of great societal concern. Various in vitro assays are available to assess adipocyte differentiation, though little work has been done to standardize protocols and compare models effectively. This study compares several adipogenic cell culture systems under a variety of conditions to assess variability in responses. Two sources of 3T3-L1 preadipocytes as well as OP9 preadip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
125
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(129 citation statements)
references
References 73 publications
2
125
0
2
Order By: Relevance
“…3T3-L1 cells were obtained from Zenbio, Inc. at passage 8 (cat# SP-L1-F, lot# 3T3062104; Research Triangle Park, NC) and were maintained in Dulbecco’s Modified Eagle Medium – High Glucose (DMEM-HG; Gibco cat# 11995) supplemented with 10% bovine calf serum and 1% penicillin and streptomycin (Gibco cat# 15140) 36 . Cells were maintained in a sub-confluent state until differentiation, and each thaw was differentiated within 8 passages (p8–15), with no significant changes in control chemical response observed in that time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3T3-L1 cells were obtained from Zenbio, Inc. at passage 8 (cat# SP-L1-F, lot# 3T3062104; Research Triangle Park, NC) and were maintained in Dulbecco’s Modified Eagle Medium – High Glucose (DMEM-HG; Gibco cat# 11995) supplemented with 10% bovine calf serum and 1% penicillin and streptomycin (Gibco cat# 15140) 36 . Cells were maintained in a sub-confluent state until differentiation, and each thaw was differentiated within 8 passages (p8–15), with no significant changes in control chemical response observed in that time.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were induced to differentiate as described in detail previously 36 . Briefly, cells were seeded into 96-well tissue culture plates (Greiner cat # 655090) at approximately 30,000 cells per well in pre-adipocyte media.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3T3–L1 cells were obtained from Zenbio, Inc. at passage 8 (cat# SPL1-F, lot# 3T3062104; Research Triangle Park, NC) and were maintained, differentiated, and maintained as described in detail previously (Kassotis et al, 2017a; Kassotis et al, 2017b). Cells were cultured in Dulbecco’s Modified Eagle Medium–High Glucose (DMEM-HG; Gibco cat# 11995) supplemented with 10% bovine calf serum and 1% penicillin and streptomycin, and were maintained in a sub-confluent state until differentiation; each thaw was differentiated within 5 passages (p9–13), with no apparent changes in control chemical response in this time.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research by our laboratory and colleagues has demonstrated significant impacts on nuclear receptor activity from samples collected in surface and groundwater near UOG spill sites in Colorado, USA (CO) (Kassotis et al, 2014), downstream from an UOG wastewater injection disposal site in West Virginia, USA (WV) (Kassotis et al, 2016b), and downstream from an UOG wastewater spill in North Dakota, USA (ND) (Cozzarelli et al, 2017). Notably, antagonism of thyroid receptor beta (TRβ) and the androgen receptor (AR) are both pathways that can influence adipogenesis (Kassotis et al, 2017a; Kassotis et al, 2017b; Niemelä et al, 2008) suggesting a potential for metabolic disruption by UOG chemicals.…”
Section: Introductionmentioning
confidence: 99%